A reading engagement-promoting strategy to facilitate EFL students' mobile learning achievement, behaviour and engagement. (29th July 2022) - Chen, Mei-Rong Alice; Hwang, Gwo-Jen; Lin, Yi-Hsuan; Abou-Khalil, Victoria; Li, Huiyong; Ogata, Hiroaki
Mobile learning (M-learning) refers to the use of mobile and wireless communication technologies to enable students to access learning materials in an interactive manner, regardless of location and time constraints. However, without a proper learning design or the provision of learning guidance, most students might fail to plan their learning schedule to effectively read and comprehend the learning materials on their own, which could significantly affect their learning engagement and outcomes. In this study, a Reading Engagement-Promotion Strategy (REPS) was proposed to tackle this issue. A quasi-experiment was designed to compare the students using the REPS approach and those using the conventional ones in terms of learning achievement, behaviours (i.e., frequency of use of markers, the number of words, and usage patterns), and engagement (i.e., time spent reading and learning). The results showed that the REPS approach could improve students' learning achievement and facilitate the high achievers' engagement.